Implications of Carbon Tax Implementation on Financial Accounting of Industrial Companies in Developing Countries - Angga Prasetia; M. Anwar Masruri; Verni Asvariwangi; Rina Rina (Brilliant International Journal Of Management And Tourism, 2025)
This study explores the implications of carbon tax implementation on the financial accounting practices of industrial companies in developing countries. Amid growing pressure to internalize environmental costs, firms face significant challenges in adapting their accounting systems to accommodate carbon liabilities, particularly in contexts with weak regulatory infrastructure. The objective of this research is to examine how carbon tax policies affect financial disclosures, cost structures, and reporting behaviors, while assessing the mediating role of sustainability reporting and the moderating effect of regulatory quality. A qualitative case study approach was employed, drawing on semi structured interviews with finance professionals and regulatory officers, complemented by document analysis of financial statements and sustainability reports. Thematic analysis revealed three core findings: (1) carbon taxes compel firms to record environmental obligations as liabilities and operational costs; (2) companies with established sustainability reporting systems demonstrate greater adaptability in integrating carbon data into financial records; and (3) strong regulatory environments enhance policy compliance and accounting transparency. These results support an integrated framework linking fiscal environmental policy, institutional quality, and financial accounting adaptation. The study concludes that the effectiveness of carbon taxation in transforming accounting practices is highly contingent on corporate reporting capacity and governance conditions. Policy recommendations emphasize the need for synchronized development of carbon tax regulations, institutional support, and adoption of international reporting standards to foster accurate and consistent environmental disclosures across the industrial sector.